Complete genome sequence of a novel bromovirus infecting elderberry (Sambucus nigra L.) in the Czech Republic - Šafářová, Dana; Candresse, Thierry; Navrátil, Milan (Archives of virology, 2018)
The genus Bromovirus currently contains six species whose members have relatively narrow host ranges. In the present work, a new bromovirus infecting elderberry (Sambucus nigra L.) is reported. dsRNA was purified and sequenced by next-generation sequencing, and with minimal additional completion by Sanger sequencing, the full tripartite genome was obtained. RNA1 is 3241 nt long and contains ORF1 (1a protein), RNA2 is 2810 nt long and contains ORF2 (2a protein), and RNA3 is 2244 nt long and contains ORF3a (movement protein) and ORF3b (coat protein, CP), separated by an intercistronic poly(A) stretch. Proteins 1a and 2a showed highest sequence identity (69.9% and 69.4%) to the corresponding proteins of melandrium yellow fleck virus. The coat protein showed highest sequence identity (67.9%) to that of brome mosaic virus. The genome shows a typical bromovirus organisation comprising of all the conserved protein domains within the genus. Phylogenetic analysis supports the assignment of this virus as a new member of the genus Bromovirus, for which the name "sambucus virus S" (SVS) is proposed.
Keywords: otevřené čtecí rámce; Base Sequence; nemoci rostlin; Genome, Viral; genom virový; RNA, Viral; Molecular Sequence Data; RNA virová; Phylogeny; bez černý; molekulární sekvence - údaje; Czech Republic; Plant Diseases; sekvence nukleotidů; Bromovirus; Česká republika; Open Reading Frames; fylogeneze; Sambucus nigra